A proposed model of non-compliance behaviour on excise duty: A moderating effects of tax agents - Sinnasamy, Perabavathi; Bidin, Zainol; Syed Ismail, Syed Soffian (Elsevier Ltd., 2015)
Taxation became a source of revenue in most of the developed and developing countries. However, tax non-compliance remains as a serious issue around the globe.The negative impact of tax non-compliance on economy and evolving nature of indirect tax in Malaysia have induced this study.The smuggling activities involved cigarettes, liquor and imported vehicles have caused a great loss to the tax revenue in Malaysia.Hence, this study attempts to propose conceptual framework by integrating tax agents as moderating effects between tax rate, penalty rate, tax fairness and peer influence with non-compliance on excise duty.